Drying effect on phytochemical and functional properties of Bougainvillea glabra flower - Ostaiza-Zambrano, Bryan (2025)
Introduction. Bougainvillea glabra is an ornamental plant that has gained scientific attention due to its medicinal potential, therapeutic properties, and toxic effects. Objective. To evaluate the effect of three drying temperatures (50, 55, and 60 °C) on the phytochemical and functional characteristics of Bougainvillea glabra flowers. Materials and methods. The analyses were conducted from July to September 2024 in Chone canton (Ecuador). Flowers were collected in self-sealing bags and transported to the Chemistry and Bromatology Laboratory of the Faculty of Agricultural Sciences (Chone), Universidad Técnica de Manabí, Ecuador. This experimental research followed a completely randomized design consisting of three treatments (T1: 50 °C, T2: 55 °C, and T3: 60 °C). Drying kinetics were studied using a FD-12 dehydrator, and moisture loss was monitored using an analytical balance. Ground samples underwent aqueous extraction through maceration and filtration. Phytochemical screening was performed, and antioxidant capacity of the plant was assessed using ABTS (2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonic acid)-diammonium salt) and DPPH (2,2-diphenyl-1-picrylhydrazyl radical) methods. Results. Higher drying temperatures resulted in greater plant material weight reduction. Phytochemical screening showed that drying temperature affected the presence of saponins and flavonoids; however, levels of tannins, free amino acids, and alkaloids remained stable. Catechins, triterpenes, reducing sugars, anthocyanins, and resins were not detected. Antioxidant activity analyses revealed that drying temperatures did not affect the DPPH results, while lower temperatures yielded higher antioxidant capacity in the ABTS method. Conclusions. Drying at 55 °C and 60 °C promoted greater weight loss, but negatively impacted the presence of saponins and catechins.